A contemporary approach to the MSE paradigm powered by Artificial Intelligence from a review focused on Polymer Matrix Composites - Gomez, C. (2021)
This paper was written in the context of the project: Desarrollo de un software para predecir el desempe no structural de product terminado en el proceso de fabricacion por manufactura aditiva de materiales compuestos founded by Cienciactiva, CONCYTEC, under the contract number No 112-2018-FONDECYT-BM-IADT-MU. The authors of this manuscript appreciate the financial support from the Peruvian Government.